2022
DOI: 10.1088/1361-665x/aca84e
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive disturbance observer-based improved super-twisting sliding mode control for electromagnetic direct-drive pump

Abstract: In this study, to enhance the frequency-flow characteristics of the novel electromagnetic direct-drive pump (EDDP). An adaptive disturbance observer-based improved super-twisting sliding mode control (ISTSMC-ADOB) is proposed to address the problem in which the response quality is deteriorated by factors such as parameter mismatch and disturbance. An adaptive disturbance observer (ADOB) is designed to achieve adaptive compensation, avoid the use of high-gain feedback, and extend the applicability of the conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 44 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…The design of an efficient control algorithm is crucial to successfully navigating the complex details of quadcopters, with the ultimate objective of maximizing their performance in various operational situations ( Li, Ge & Lee, 2021 ; Zhang, Zhou & Li, 2023 ; Zhang et al, 2023 ). This approach guarantees both stability and precision during flight and highlights the ongoing development of control methods to meet the changing requirements of unmanned aerial vehicle technology ( Shi et al, 2023 ; Chen et al, 2022 ; Lu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 94%
“…The design of an efficient control algorithm is crucial to successfully navigating the complex details of quadcopters, with the ultimate objective of maximizing their performance in various operational situations ( Li, Ge & Lee, 2021 ; Zhang, Zhou & Li, 2023 ; Zhang et al, 2023 ). This approach guarantees both stability and precision during flight and highlights the ongoing development of control methods to meet the changing requirements of unmanned aerial vehicle technology ( Shi et al, 2023 ; Chen et al, 2022 ; Lu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 94%
“…Some researchers have presented the two-phase DC–DC, where one phase is a GaN-based transistor while another phase is a SiC-based MOSFET 24 . A design of a 15,000W DC/DC converter along with LLC topology as SiC devices to decrease the power loss with high efficiency 25 . They showed that their proposed converter was 98.4%, which is 3% higher than the conventional converter.…”
Section: Related Workmentioning
confidence: 99%
“…Compared with second-order algorithms such as twisting algorithm, sub-optimal algorithm, prescribed convergence law algorithm, quasi-continuous algorithm, and drift algorithm, to weaken the shortcomings of traditional SMO chattering problems as much as possible, A. Levant proposed a super-twisting algorithm theory. References 42 , 43 concluded that the super-twisting algorithm converges in finite time and improves robustness in the case of disturbance and no disturbance. The super-twisting algorithm has the advantage that it does not need to calculate the derivative and extremum of the sliding mode variable.…”
Section: Design Of Fuzzy Super-twisting Sliding Mode Observermentioning
confidence: 99%